Integration between genetic and chemical control on the progress of Asian soybean rust and yield - Sacon,Deivid (2020)
ABSTRACT The objective of this study was to evaluate the genetic control integrated to the chemical control of Asian soybean rust (ASR) and the effects of these measures on crop yield. The experiment was conducted in Erechim, Rio Grande do Sul State, Brazil, in 2016/17 and 2017/18 crop years, under a randomized block design, in a subdivided plot scheme (cultivars in the plots and fungicides in the subplots), with four replicates. The following cultivars were used: BMX Vanguarda (without ASR tolerance); TMG 7062; TMG 7262, and TMG 7161, tolerant to ASR (Inox™ Technology cultivars). The fungicides used were: T1) control (without application of fungicides); T2) azoxystrobin + benzovindiflupyr; T3) difenoconazole + cyproconazole; T4) trifloxystrobin + prothioconazole, and T5) epoxiconazole + fluxapyroxad + pyraclostrobin. Four fungicide applications were carried out at the V6, R1, R5.1 and R6 stages. During the experiment, for the calculation of the area under disease progress curve (AUDPC), disease severity was assessed at 7-day intervals in a random sample of 10 trifolia per plot. After harvest, yield components were determined: number of grains per plant, thousand grain weight (g), and yield (kg ha-1). In 2017/18 crop year, the fungicide difenoconazole + cyproconazole was not efficient for ASR control. The soybean cultivars TMG 7062, TMG 7161 and TMG 7261 delayed the disease progression; however, only TMG 7161 presented tolerance in the presence of the inoculum in 2016/17 and 2017/18 crop years. The association between chemical and genetic control is shown to be efficient for ASR control.